Configurable Miniaturized 3D Pores for Robust Single‐Nanoparticle Analysis. Issue 2 (13th November 2020) - Liao, Caizhi; Antaw, Fiach; Wuethrich, Alain; Anderson, Will; Trau, Matt
Abstract : Resistive‐Pulses Sensing In article number 2000011, Alain Wuethrich, Will Anderson, Matt Trau, and co‐workers develop a facile strategy for the fabrication of tailored resistive‐pulses sensing (RPS) pores by two‐photon nanolithography. Symbolized by the Chinese Yin Yang, the right balance of photon intensity of the laser beam and scanning speed generates powerful and accurate three‐dimensional (3D) RPS pores that are as enticing as the ancient tripod Ding. These 3D pores enable fingerprinting analysis of individual nanoparticles by RPS, opening up exciting applications for single biomolecule interrogations.